Antimicrobial Stewardship Program Implementation among Hospitals in Iloilo Province, Philippines - A Pilot Study - Dueñas, Edric Ancel P.; Islahudin, Farida (Asian journal of pharmaceutical research and health care, 2024)
ABSTRACT Context: Antimicrobial resistance (AMR) presents a global health crisis, demanding urgent attention. The Philippines has responded with an action plan, including Antimicrobial Stewardship Programs (ASPs), to combat AMR. However, challenges persist in implementing effective ASPs. Aims: This study aims to evaluate the implementation of ASP in Iloilo Province, Philippines. Settings and Designs: The study was a cross-sectional study performed in hospitals (n = 14) within the Iloilo Province, Philippines. Incomplete questionnaires were excluded. Subjects and Methods: The research employed the World Health Organization ASP toolkit to assess ASP implementation levels in these hospitals. Statistical Analysis Used: Implementation was measured using an overall score and individual scores for 6 core elements of ASP. Scores were presented as mean and standard deviations. Results: A total of 10 hospitals responded. All 10 (100%) hospitals had implemented the ASP, although the overall implementation score was an average of 31.9 (7.9) (total possible score of 45). However, there were still gaps in the implementation of all 6 core elements: Leadership Commitment (8.1 [1.2], total possible score 11), accountability and responsibility (6.3 [0.8], total possible score 8), antimicrobial stewardship action (9.8 [3.3], total possible score 14), training and education (1.2 [0.8], total possible score 2), monitor and surveillance (2.7 [1.2], total possible score 4), and reporting and feedback (3.8 [2.3], total possible score 6). Conclusions: There is still a need to improve ASP implementation among hospitals in Iloilo Province and possibly nationally in the Philippines. National strategies to address potential barriers that may aid in improving the use of antimicrobials are urgently required.